The mastery of Malay language among Tamil school students - Munuyandi, Thulasirani; Husain, Salina; Abdul Jabar, Mohd Azidan; Jusoh, Zuraini (Otago Polytechnic, 2024)
This analysis centers on characterizing the degree of verbal mastery of the verb in the Malay language using the questionnaire by Tamil school students. The target of study is to assess the verb mastery in Malay language among Tamil school students through the use of Test application. Besides, this study analyzed the factors that influence verb dominance in the Malay language. The quantitative survey research design was utilized to convey questionnaires among 100 Tamil students. The outcomes show that Tamil students are as yet weak on Malay verb data while utilizing the test (N = 1.96; SD = 0.46). This shows that Tamil students are as yet unfit to offer enormous displays and are truly impacted by their primary language. Its essentials are feeble in Malay because of its attitude, absence of teaching materials, teacher attitude, and parental point of view. The consequences of this study shows that all groups ought to assume a part in further developing the verb dominance of the Malay verb utilized by Tamil students. This implies that they don't keep away from training, particularly in issues of the Malay language. Later on the verb mastery of English language can be investigated using test application.